Acoustic vortices for artificial microtissue: A proof-of-concept study - 김형민; 최원석; 박혜원; 윤인찬; 윤태영영; 한성민 (2024년도 제63회 대한의용생체공학회 춘계학술대회, 2024)
Although conventional approaches to forming microtissues are more suitable for mimicking in vivo microenvironement compared to two-dimensional cultivation, several drawbacks including low yield, nonuniformity in size and shape, and costs for labor are still problematic. Here as a proof-of-concept study, we introduce the size and shape-controllable approach for fabricating artificial microtissue by transferring orbital angular momentum in suspension and analyze the efficacy in formation of microtissue in the aspect of acoustic parameters. The geometrical specification of developed 4-panel focused transducer generated the absolute zero pressure region in center, thereby potentially trapping cancer cells. This approach can not only facilitate the formation of microtissues in the shape of spheroids, but it can also support the formation of microtissues in rod-like structures by finely modulating pulsing parameters.